SCDT-36. NOVEL MODULAR, PERMANENTLY IMPLANTED COLLAGEN-BASED DEVICE FOR INTRAOPERATIVE BRACHYTHERAPY IN PATIENTS WITH CENTRAL NERVOUS SYSTEM TUMORS - Youssef, Emad (Neuro Oncol, 2017)
BACKGROUND PROBLEM: Brachytherapy (BT) is a current standard of care treatment for many non-central nervous system (CNS) tumors, but is rarely used for as an adjuvant CNS tumor treatment. Combining surgical resection with adjuvant BT in brain tumors represents an attractive therapeutic option as immediate post resection radiation could evince a higher therapeutic ratio in rapidly proliferating tumors, BT using a short-range isotope exposes less normal tissue to radiation than EBRT (possibly limiting neurocognitive deficits), and source placement under intraoperative visualization allows more precise identification of the area at risk than does post-operative treatment imaging. Major challenges in brain brachytherapy have been 1) the occurrence of radiation “hot spots” and “cold spots” resulting from uneven spacing of radiation sources (called “seeds”) and direct seed-to-brain contact, and 2) the poor handling qualities of the seeds themselves, 4.5 mm x 0.8 mm radioactive cylindrical titanium capsules. Radiation hot spots and direct seed-to-brain contact can result in excess radiation and injury, and radiation cold spots that receive too little radiation may lead to tumor persistence. SOLUTION: To overcome these draw-backs we designed the GammaTile™. The GammaTile™ is a modular, permanently implanted collagen-based device designed to function simultaneously as a three-dimensional spacer and multi-seed carrier, preventing seeds from harmful direct contact with the brain, maintaining source geometry, eliminating seed migration, and facilitating rapid implant completion. We utilized Cesium-131, a low energy (28 kV), short half-life (9.7 days) isotope as rapid decay may offer a biological advantage in treatment of rapidly proliferating tumors. Using GammaTile™, the radiation dose in the first few millimeters of the operative bed is 90-120 Gy, 1.5-2 times greater than the 60Gy typically achieved by fractionated EBRT. We have initiated a proof of concept trial of resection plus BT (NCT#03088579) utilizing a prototype device which has enrolled >100 patients to date.